A review on occurrence and analytical procedures for the evaluation of polychlorinated naphthalenes in human and environmental matrices. Issue 1 (1st January 2020) - Agunbiade, Idowu Victoria; Adeniji, Abiodun Olagoke; Okoh, Anthony Ifeanyi; Okoh, Omobola Oluranti
ABSTRACT: Polychlorinated naphthalenes (PCNs) are organochlorine compounds comprising the naphthalene ring system, in which one to eight hydrogen atoms have been substituted with chlorine atoms, yielding 75 chlorinated congeners. They were considered as persistent organic pollutants in May 2015 at the Stockholm Convention owing to their toxicity, persistence, bioaccumulation and potential for long-range transport in the environment. PCNs were invented in the early 1900s to be applied as flame-retardants in consumer products. Flame-retardants are effective in minimizing fire-related problems. However, their negative environmental impacts have become of great concerns. Different analytical methods for the evaluation of PCNs in various environmental samples were reviewed in this article.. Their levels in human and some environmental samples across the globe are also mentioned. Reported data revealed that the highly toxic congeners (CNs 66, 67 and 73) are prevalent in most samples, there is need for their continuous monitoring in our environment.